1986
DOI: 10.1080/00480169.1986.35334
|View full text |Cite
|
Sign up to set email alerts
|

Equine laryngeal hemiplegia part I. A light microscopic study of peripheral nerves

Abstract: This light microscopic investigation of 15 Thoroughbred horses provided substantial evidence for the classification of equine laryngeal hemiplegia as a distal axonopathy. Morphologic and morphometric examinations were performed on resin embedded recurrent laryngeal nerves from control, subclinical and clinical laryngeal hemiplegic animals. In the latter group of animals some distal hindlimb nerves were also examined. A distally graded loss of myelinated fibres selectively affecting those of large diameter was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 14 publications
3
63
0
1
Order By: Relevance
“…supplied by this nerve. 5,6,[15][16][17] Studies on the histologic changes that occur in laryngeal muscles of affected horses have aided in understanding the progression and clinical presentation of the disease, but the molecular level events that occur in RLN have not been studied. An understanding of the changes in protein expression in affected muscles may help clarify the pathogenesis of this disease and develop future strategies for treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…supplied by this nerve. 5,6,[15][16][17] Studies on the histologic changes that occur in laryngeal muscles of affected horses have aided in understanding the progression and clinical presentation of the disease, but the molecular level events that occur in RLN have not been studied. An understanding of the changes in protein expression in affected muscles may help clarify the pathogenesis of this disease and develop future strategies for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…10,13,23 Studies have shown histologic evidence of ongoing demyelination and remyelination of the recurrent laryngeal nerve as a result of a continual injury and attempts at nerve repair and, therefore, likely ongoing axonal injury as well. 6,16 A population of affected horses selected at one given timepoint would have varying degrees of muscle atrophy as an endstage event with ongoing nerve injury. Future studies to confirm the altered MHC composition in affected horses may be performed on horses with experimentally induced RLN, which would eliminate the variation in the course of the disease at the time of sample collection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies had shown that the distal axonopathy affected the left adductors (i.e., the L-TrAs) more severely than the left abductor (L-CAD). Further, the right recurrent laryngeal nerve was sometimes also affected, albeit less severely than the left (Cahill and Goulden 1986a;Duncan et al 1991a;Lopez-Plana et al 1993;Hahn et al 2008). Thus, among the muscles studied, the L-TrA muscle would be the most sensitive for detecting the presence of fibertype grouping.…”
Section: Immunohistochemistry and Division Of Muscle Intomentioning
confidence: 99%
“…There is now considerable evidence that this condition results from loss of large-diameter myelinated axons that is most profound distally (described as a distal axonopathy) in the left recurrent laryngeal nerve (Duncan et al 1974;Cahill and Goulden 1986a;Hahn et al 2008). The subsequent laryngeal muscle denervation and atrophy, which gives rise to the clinical signs of incomplete abduction of the arytenoid cartilage and vocal cord, is therefore typically left-sided.…”
mentioning
confidence: 99%